(3GdSdWI aj GdeLJeY GdGTJQGcj (B/s - (3UHMj YHOg SYjOs; (3WYjeI GdLQas; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 1980)
(3JHOC gPg GdQSGdI HHGH JegjOj Yf GdSdWI heG JKjQg ef eTcdGJ, Ke JfbSe Edi KdGKI CHhGH ; MjK jJfGhd GdHGH GdChd Gdbhi GdSjGSjI UGMHI GdSdWI aj GdeLJeY GdGTJQGcj, Ke GdHGH GdKGfj Yf eeGQSI GdSdWI hfXQjI GdMcheI aj GdeLJeY GdGTJQGcj, hCNjQG GdHGH GdKGdK Yf eLGdGJ GdSdWI hMOhOgG aj GdeLJeY GdGTJQGcj(B.s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B1980.s
(3jTJed Ydi EQLGYGJ HjHdjhLQGajI UaMGJ (B525 - 553.s
Keywords: (3GdbGfhf GdOSJhQjs; (3GdeLJeY GdGTJQGcjs; (3GdGTJQGcjIs; (3Gdbhi GdSjGSjIs; (3GdOjebQGWjI s; (3GdJfXje GdSjGSjs; (3GdSdWI GdGTJQGcjI hGdeYGQVIs; (3GdGTJQGcjI GdeGQcSjIs; (3acQI GdELeGY GdSjGSjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs